College Algebra (11th Edition)

Published by Pearson
ISBN 10: 0321671791
ISBN 13: 978-0-32167-179-0

Chapter 1 - Section 1.6 - Other Types of Equations and Applications - 1.6 Exercises - Page 134: 15



Work Step by Step

$$\frac{2x+1}{x-2}+\frac{3}{x}=-\frac{6}{x(x+2)}$$ $$(x(x-2))(\frac{2x+1}{x-2}+\frac{3}{x})=(x(x-2))(-\frac{6}{x(x+2)})$$ $$x(2x+1)+3(x-2)=-6$$ $$2x^2+x+3x-6=-6$$ $$2x^2+4x=0$$ $$x^2+2x=0$$ $$x(x+2)=0$$ $$x=0,-2$$ 0 is an extraneous solution. $$x=-2$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.